Cortical Hemodynamic Response and Connectivity Modulated by Sub-threshold High-Frequency Repetitive Transcranial Magnetic Stimulation - Li, Rihui; Potter, Thomas; Wang, Jun; Shi, Zhixi; Wang, Chushan; Yang, Lingling; Chan, Rosa; Zhang, Yingchun (Frontiers in Human Neuroscience, 2019)
Repetitive Transcranial Magnetic Stimulation (rTMS) at sub-threshold intensity is a viable clinical strategy to enhance the sensory and motor functions of extremities by increasing or decreasing motor cortical excitability. Despite this, it remains unclear how sub-threshold rTMS modulates brain cortical excitability and connectivity. In this study we applied functional near-infrared spectroscopy (fNIRS) technique to investigate the alterations in hemodynamic responses and cortical connectivity patterns that are induced by high frequency rTMS at a sub-threshold intensity. 40 high frequency (10 Hz) trains of rTMS at 90% resting motor threshold (RMT) were delivered through a TMS coil placed over 1-2 cm lateral from the vertex. FNIRS signals were acquired from the frontal and bilateral motor areas in healthy volunteers (n=20) during rTMS administration and at rest. A significant reduction in oxygenated hemoglobin (HbO) concentration was observed in most defined regions of interest (ROIs) during the stimulation period (p < 0.05). Decreased functional connectivity within prefrontal areas as well as between symmetrical ROI-pairs was also observed in most participants during the stimulation (p < 0.05). Results suggested that fNIRS imaging is able to provide a reliable measure of regional cortical brain activation that advances our understanding of the manner in which sub-threshold rTMS affects cortical excitability and brain connectivity.